The Strategic Role of Christian Bible or Theological Colleges in Religious Moderation in Muslim Majority Society - Andreas Jonathan (Journal of Religious and Socio-Cultural, 2025)
Religious moderation remains highly relevant in Indonesia today, as intolerance and extremism continue to emerge and affect various sectors, including higher education and students as the younger generation. Interfaith dialogue is one of the approaches widely used to promote moderation; however, such initiatives are often incidental and have limited impact in transforming individuals from intolerance to tolerance, or from social exclusivism to social pluralism. This study aims to address these weaknesses by examining the transformation process of students who actively participate in interreligious student communities. In addition, it seeks to explore and propose the strategic role of Bible/Theological Colleges (B/TC) in Indonesia in supporting religious moderation efforts. Employing a qualitative approach through interviews, direct observation of interfaith student activities, and literature review, the research finds that sustainable interfaith communities are more effective than incidental dialogues in fostering openness, tolerance, and mutual respect among students of different faiths. The findings indicate that B/TC should not limit their role to serving Christian communities but must also contribute to the common good by collaborating with Islamic Religious Higher Education institutions in establishing long-term interfaith student communities. This study contributes by offering an alternative model of interfaith engagement that strengthens the effectiveness of religious moderation initiatives in Indonesia and provides practical insights for religious higher education institutions in promoting social harmony.